Justification of the project a network of freight terminals unitized cargo - Ilesaliev D.I. (Научно-технический вестник Брянского государственного университета)
In this paper we consider the question of Uzbekistan in promoting the development of international transport in supply chains. The development of transport infrastructure to ensure timely delivery of goods is one of the main tasks in supply chain management. The aim is to study of the project network terminal unitized cargo Uzbekistan in supply chains. Methods the study is based on analysis of existing methods and techniques of Russian scientists in the field of place-ment of objects. The method of searching the most rational location of logistics facility in the supply chain. Also pre-justified the project network terminal unitized cargo in Uzbekistan. Given the state of the problems and prospects of transport logistics of Uzbekistan, the developed method can be used by experts when performing the supporting calcula-tions location of logistic objects.